Prospects of MXenes in energy storage applications - Lokhande, P. E.; Pakdel, Amir; Pathan, H. M.; Kumar, Deepak; N. Vo, Dai-Viet; Al-Gheethi, Adel; Sharma, Ajit; Goel, Saurav; Pratap Singh, Prabal; Lee, Byeong-Kyu (Elsevier, 2022)
The transition metal carbides/nitrides referred to as MXenes has emerged as a wonder material presenting newer opportunities owing to their unique properties such as high thermal and electrical conductivity, high negative zeta-potential and mechanical properties similar to the parent transition metal carbides/nitrides. These properties of MXenes can be utilized in various societal applications including for energy storage and energy conversion. In this focused review, we provide a ready glance into the evolutionary development of the MXene family and various efforts that are made globally towards property improvement and performance enhancement. Particular attention in this review is made to direct the attention of readers to the bright prospects of MXene in the energy storage and energy conversion process – which is extremely timely to tackle the current concern on climate change. The review concludes by offering fresh insights into the future research needs and challenges that need to be addressed to develop resilient energy solutions.